LITERATUR REVIEW: PENGARUH YOGA DAN OBAT HERBAL PADA SAAT MENOPAUSE: LITERATURE REVIEW: INFLUENCE OF YOGA AND HERBAL MEDICINE AT MENOPAUSE - Sunarsih, Tri Sunarsih; Annisa Alfitri; Erni Kurniawati; Nurviyanti Octavia (Politeknik Insan Husada Surakarta, 2024)
Background: Menopause is a natural phase in a woman's life which is marked by the permanent cessation of menstruation. During menopause, significant hormonal changes occur in a woman's body, which can cause certain symptoms and health effects. In an effort to reduce symptoms and maintain health holistically, many women seek alternative treatments such as yoga and the use of herbal medicine. Purpose: To determine the effect of yoga and herbal medicine on menopausal hypertension. Method: used in writing this article is a literature review. Namely a literature search both international and national which was carried out using the Google Scholar database, National Library of Indonesia, Mendeley, PubMed. In the early stages of journal articles, 354 articles were obtained from 2018 to 2022 using the keywords